Development of adverse outcome pathways relevant for the identification of substances having endocrine disruption properties Uterine adenocarcinoma as adverse outcome. (14th February 2023) - ,; Hernandez‐Jerez, Antonio F; Adriaanse, Paulien; Aldrich, Annette; Berny, Philippe; Coja, Tamara; Duquesne, Sabine; Focks, Andreas; Millet, Maurice; Pelkonen, Olavi; Pieper, Silvia; Tiktak, Aaldrik; et al.
Abstract: Development of adverse outcome pathways (AOPs) for uterine adenocarcinoma can provide a practical tool to implement the EFSA‐ECHA Guidance (2018) for the identification of endocrine disruptors in the context of Regulations (EU) No 528/2012 and (EC) No 1107/2009. AOPs can give indications about the strength of the relationship between an adverse outcome (intended as a human health outcome) and chemicals (pesticides but not only) affecting the pathways. In this scientific opinion, the PPR Panel explored the development of AOPs for uterine adenocarcinoma. An evidence‐based approach methodology was applied, and literature reviews were produced using a structured framework assuring transparency, objectivity, and comprehensiveness. Several AOPs were developed; these converged to a common critical node, that is increased estradiol availability in the uterus followed by estrogen receptor activation in the endometrium; therefore, a putative AOP network was considered. An uncertainty analysis and a probabilistic quantification of the weight of evidence have been carried out via expert knowledge elicitation for each set of MIEs/KEs/KERs included in individual AOPs. The collected data on the AOP network were evaluated qualitatively, whereas a quantitative uncertainty analysis for weight of the AOP network certainty has not been performed. Recommendations are provided, including exploring further the uncertainties identified in the AOPs and putative AOP network; further methodological developments for quantifying the certainty of the KERs and of the overall AOPs and AOP network; and investigating of NAMs applications in the context of some of the MIEs/KEs currently part of the putative AOP network developed. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2023.EN-7748/full